Pengaruh Model Problem Based Learning Berbasis Kearifan Lokal Terhadap Keterampilan Berfikir Kritis Siswa Kelas IV Sekolah Dasar - Lestari, Vionita; Imansyah, Farizal; Fakhrudin, Ali (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This research is a quantitative research with experimental research methods. This study aims to determine the effect of using problem based learning model based on local wisdom on critical thinking skills of fourth grade elementary school students. The problem behind this research is that in the implementation of learning the teacher has implemented a learning model such as discussion, but in practice the teacher does not follow the procedure, so it looks like a normal discussion. And the lack of application of learning that uses local wisdom so that students are less trained to think critically in solving problems. The subjects of this study were students of class IVA and IVB. The instrument of data collection used the instruments of questions, observations, and documentation. The results showed thatthere was a significant effect of the problem based learning model based on local wisdom on the critical thinking skills of grade IV students, because it was proven that the average score for the experimental class was 88.1 and the average value for the control class was 83.1 with a level the t-test significance of 0.000 is less than 0.05 or (0.000 < 0.05) which states that Ho is rejected and Ha is accepted.